Role of Otoacoustic Emissions and Auditory Brainstem Response for Early Detection of Hearing Loss in Children 0-3 Months of Age - Hemant Gupta; Smriti Anand; Neelam Grover; Vipen Gupta; Deepika Sharma (Asian Journal of Clinical Pediatrics and Neonatology, 2019)
Background: Hearing impairment has a huge adverse impact on the normal developmental outcome of an individual. The various newborn period risk factors may escalate hearing loss. Early detection of hearing impairment has been made possible with the use of universal tools like OAE (Otoacoustic emission) and ABR (Auditory brainstem response) and has resulted in the general awareness and timely intervention. This study highlights the use of OAE and ABR for early detection of hearing loss in children 0-3 months along with the associated risk factors taken into consideration.Subjects and Methods: The present study was conducted in Maharishi Markandeshwar medical college and hospital over a period of 12 months and included 1680 newborns who were subjected to two staged OAE examination( pre discharge and at 6 weeks) followed by ABR examination done over a period of 3 months. The various risk factors were also evaluated.Results: A total of 1680 newborns underwent pre discharge first OAE examination, 146(8.7%) failed. A total of 141 underwent the repeat OAE examination at 6 weeks and 23(16.3%) failed. ABR examination of 20 children resulted in failure in 3(15%) culminating in overall prevalence of hearing impairment of 1.79 per 1000 population. The prevalence of various risk factors taken into consideration was 23%.Conclusion: The two staged sequential OAE assessment followed by ABR examination has an important role for the early detection of hearing impairment and consequent improvement in the quality of life. This should be adopted by all the newborn care providers as a part of their routine examination of the newborns.